It Was Not Just a Stomachache! (Comparative & International Education Series, 2022)
I began writing this piece on October 03, 2021. A year ago, that day, I underwent a sudden appendix removal surgery, one of the worst nightmares for any international student in a foreign land. Similar to the present day, it was also a gloomy weekend in Athens, Georgia, United States. I was returning to classes after the midterm of the first semester in my doctoral program. After lunch and a 10-minute afternoon nap, pain erupted in my stomach. I first thought it was a new chicken brand I bought last week that is not suiting me. It has happened to me before, thanks to my sensitive body. Feeling as if a lost needle was slightly poking in the right of my abdomen, I looked for my mighty bottle of Hajmola, an Indian brand of digestive tabs, I brought from Patel Brothers some weeks ago. After popping four pupil-sized tabs, I thought the pain would subside soon. Little did I know what wreathing pain was waiting for me.